PENGARUH KEPEMIMPINAN KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI BADAN PERTANAHAN NASIONAL KABUPATEN KLUNGKUNG - Gde Bayu Surya Parwita; Made Ika Prastyadewi; Putu Indah Cahyani (VALUES, 2024)
This study aims to test and analyze the influence of leadership, compensation, organizational culture on employee performance. This research was conducted at the Klungkung Regency National Land Agency with a research sample of 89 respondents who were taken using saturated sampling techniques. All data obtained from the distribution of questionnaires is feasible to use, then analyzed using multiple linear regression, hypothesis testing (t test and f test). The results showed that (1) Leadership has a positive and significant effect on Employee Performance at the Klungkung Regency National Land Agency Office, so that the better the Leadership, the more employee performance will increase at the Klungkung Regency National Land Agency Office (2) Compensation has a positive and significant effect on Employee Performance at the Klungkung Regency National Land Agency Office so that the more compensation increases, the more employee performance will increase at the Klungkung Regency National Land Agency Office (3) Organizational Culture has a positive and significant effect on Employee Performance at the Klungkung Regency National Land Agency Office, so that the better the Organizational Culture, the more employee performance will increase at the Klungkung Regency National Land Agency Office.